Urgensi Pengembangan Sumber Daya Manusia (SDM) Holistik dalam Perspektif Pendidikan Islam di Era Disrupsi Digital - Sudarmono Sudarmono; A. Marjuni; Afifuddin Harisah (Lembaga Pengembangan Kinerja Dosen, 2026)
Globalization and digital disruption require Islamic education institutions to strengthen human resource development in order to remain relevant to contemporary societal and labor market demands. Human resource development in Islamic education faces challenges related to technological adaptation, curriculum relevance, and the integration of values with professional competencies. This study aims to analyze human resource development theories from the perspective of Islamic education, examine cognitive, affective, and psychomotor learning outcomes, and identify challenges in developing human resources in the era of digital disruption. This research employed a qualitative approach using library research through a systematic review of relevant books and scholarly journal articles published between 2020 and 2025. The findings indicate that human resource development in Islamic education requires a holistic approach that integrates knowledge mastery, character formation, and practical skills. The study also identifies key challenges, including limited digital competence among educators, unequal technological infrastructure, and curriculum alignment with contemporary demands. The implications highlight the need for strategic repositioning of human resource development in Islamic education to respond to digital disruption while maintaining Islamic values.